Biochemical and in-silico Insights into the Cardioprotective Potential of Agaricus bisporus through NF-κB and Keap1/Nrf2 Pathway Modulation - M. O. Enemali; A. A. Oladejo; C. B. Okeke (Journal of Advances in Medicine and Medical Research, 2026)
Background: Myocardial infarction is associated with oxidative stress, cellular injury and dysregulation of inflammatory signalling. Agaricus bisporus contains diverse bioactive constituents with reported antioxidant and pharmacological activities, but its cardioprotective effects and possible molecular mechanisms remain incompletely characterised. Aim: This study investigated the cardioprotective activity of A. bisporus fractions in isoproterenol-induced myocardial infarction using in vivo and in silico approaches. Methods: Fresh A. bisporus was sequentially extracted to obtain n-hexane, ethyl acetate, ethanol and aqueous fractions. Wistar rats were pretreated orally with each fraction at 100, 200 or 400 mg/kg for 14 days before myocardial injury was induced with isoproterenol (150 mg/kg, intraperitoneally) on two consecutive days. Lisinopril-treated, isoproterenol-induced and normal groups served as controls. Serum catalase (CAT), superoxide dismutase (SOD) and lactate dehydrogenase (LDH) activities were determined. Molecular docking was subsequently performed using AutoDock Vina to evaluate the interactions of selected A. bisporus phytoconstituents with NF-κB and Keap1. Results: Isoproterenol administration markedly reduced SOD activity and increased LDH activity relative to the normal control, indicating oxidative imbalance and myocardial cellular injury, while CAT activity showed comparatively modest changes. Treatment with A. bisporus fractions produced variable, fraction- and dose-dependent effects. The 400 mg/kg ethanol fraction produced the most pronounced increase in SOD activity (104.12 × 10⁻⁶ U/mL), whereas the 400 mg/kg ethyl acetate fraction produced the lowest LDH activity (225.54 U/L). Molecular docking revealed favourable interactions of several investigated phytoconstituents with the target proteins. Rutin exhibited the strongest predicted binding affinity towards NF-κB (−7.4 kcal/mol) and Keap1 (−9.6 kcal/mol), while myricetin and quercetin also demonstrated strong predicted interactions with Keap1 (−9.5 kcal/mol each). Conclusion: Agaricus bisporus fractions demonstrated promising cardioprotective potential against isoproterenol-induced myocardial injury, particularly through modulation of antioxidant defence and reduction of cellular injury. The docking findings further suggest that phytoconstituents such as rutin, myricetin, quercetin, catechin and epigallocatechin may contribute to these effects through interactions with NF-κB and Keap1. Further experimental studies are required to validate these predicted molecular mechanisms and identify the specific bioactive constituents responsible for the cardioprotective activity.